Persinggungan Politik Kolonialisme Jepang Terhadap Umat Islam di Hindia-Belanda 1942-1945 - Hidayatullah, Achmad; Khoiri, Miftahul; Sodikin, Ahmad; Utomo, Ria Auliya (Universitas Islam Internasional Darullughah Wadda'wah, 2023)
This article examines the Japanese occupation of Muslims in the Dutch East Indies (Indonesia). The purpose of writing this article is so that the Indonesian people, especially the Muslim community today, understand the contribution of their predecessors who were persistent in dealing with colonialism, including the Japanese political occupation of Muslims. This article is a combination of field studies and literature, using historical methods namely, heuristics, criticism, interpretation, and historiography. The results of this study indicate that the arrival of the Japanese in the Dutch East Indies was motivated by Japan's involvement in World War II and the Greater East Asia War. In this case, encouraging the Samurai to invade the land of the Dutch East Indies looking for ammunition in the form of oil as a fuel for tools, as well as looking for time as troops to help. Arriving in the land of the Dutch East Indies, Japan was fascinated by the Muslims in the Dutch East Indies, because it was considered that Muslims in the Dutch East Indies had more adherents than other religions. In addition, Islamic teachings are considered to have similarities with the Japanese way of life. The Japanese who invaded the land of the Dutch East Indies, he implemented government policies in the form of mobilization and control, with the aim of moving the masses and preparing internal troops, but their movements were still under the control of the Japanese occupation. In addition, in the field of religion, the Indonesian Muslim Shura Council. Japanese politics has given birth to several laskars of ulama and santri born from the Defenders of the Homeland (PETA), as well as Laskar Hezbollah, so that Muslims developed during the occupation.